Improving the training of managers in the sphere of physical culture and sports in Ukraine - Stadnik, S. O.; Prikhodko I. P. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Analyzed contemporary research on the training of managers in the sphere of physical culture and sports in Ukraine and abroad. Analyzed 50 references, which dealt with various aspects of the preparation of sports managers. It was found that in higher education of Great Britain, Germany, France, Switzerland, Russia is working to prepare managers for the sphere of physical culture and sports. It was found that training of managers in Ukraine is carried out only on the basis of two universities. Found that the content of the training of sports managers in our country needs to be improved, taking into account international experience and current market conditions of the functioning of sports organizations. Identified the main ways of improving the training of managers in the sphere of physical culture and sports in Ukraine.